AVALIAÇÃO DA TRATABILIDADE DE EFLUENTE DA PISCICULTURA PELOS SISTEMAS DE FILTRO BIOLÓGICO E WETLANDS CONSTRUÍDOS - SANTINI, TIAGO ANTONIO (2022)
When studying Wetlands systems and their constructive way, one can observe a variety of different flow flows, support media and macrophytes used, most experiments show a high efficiency in wastewater treatment processes. The objective of this work was to apply, on a pilot scale, the treatment of effluent from fish farming, comparing the efficiency of three different systems, Biological Filter, Vertical Flow Wetland and Vertical Flow Wetland with Effluent Recirculation System, both experiments having the same volume (50 liters) and medium support (gravel), the systems received 30 liters of effluent to be treated, the hydraulic detention time used was 2 hours for a total period of 24 hours and the physical chemical parameters analyzed were: Phosphorus ( P), Dissolved Oxygen (DO), Potential Hydrogen (pH), Total Solids (ST) and Apparent Color (uH). The macrophyte used in the Wetlands beds was of the Syngonium podophyllume species, as an operating strategy the samples of the three systems were collected every 2 hours and submitted to analysis at the Environmental Engineering department of UNICENTRO campus Irati – PR. In general terms, the studied treatment systems showed a significant gain in the treatment of the fish farming effluent, a high removal of phosphorus (91.98%), pH stabilization (7.88%), elevation of dissolved oxygen (90.54% ), reduction of total solids (84.38%), as well as improvement of the visual aspect through the clarification of the effluent after treatment in the Wetlands systems (82.40%), demonstrating that the use of these systems in full scale becomes promising and that the treatments can be maximized with the use of complementary systems of aeration and recirculation of the effluent in the system.